A Critical Review on the Book “Why Nations Fail: The Origins of Power, Prosperity, and Poverty” - Hamid Reza Maghsoodi; Mohammad Javad Masoominia (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “Why Nations Fail: The Roots of Power, Wealth and Poverty" written by Daron Ajmoglu and James E. Robinson is one of the works of new institutionalism. By examining the history of nations, the authors have analyzed the reasons for the growth and decline of societies. This work, like other works of the authors, is based on the comparative study of the long-term development experience of different nations. In this article, while examining the formal structure and quality of the translation of the book, which was done by Mohsen Mirdamadi and Mohammad Hossein Naimipour, the content of the book has also been examined. The book has content and methodological weaknesses. The authors claim to have derived their theory with a historical approach and an inductive method, but in fact, by choosing oriented analytical and comparative methods and of course philosophical ones, they have presented an ideological reading of the history of countries and the quality of their development. The lack of statistical evidence and the contention of the analytical method and repeated emphasis on the author's opinion with repeated identifications have weakened the content of the book. Claiming to be inductive and rejecting this claim by using an analogical approach is one of the most important problems of this book. The book has a fluent translation, but it has many editing problems. The design of its cover and back cover unfairly evokes a black, defeated, and poor image of the people of Iran.